Jahrbuch für Wissenschaft und Ethik (De Gruyter, 1996)
The Jahrbuch für Wissenschaft und Ethik aims to provide an academic forum to promote interdisciplinary discussion of the ethical questions arising from modern developments in science and technology. Each volume contains original papers, conference reports and important documents by national and international institutions.